Complications After Total Skin-Sparing Mastectomy and Expander-Implant Reconstruction: Effects of Radiation Therapy on the Stages of Reconstruction. Issue 1 (January 2018) - Peled, Anne Warren; Sears, Marie; Wang, Frederick; Foster, Robert D.; Alvarado, Michael; Wong, Jasmine; Ewing, Cheryl A.; Sbitany, Hani; Esserman, Laura J.; Fowble, Barbara
Abstract : Background: Many patients undergoing total-skin sparing mastectomy (TSSM) and 2-staged expander-implant (TE-I) reconstruction require postmastectomy radiation therapy (PMRT). Additionally, many patients undergoing TSSM for recurrent cancer have a history of lumpectomy and radiation therapy (XRT). Few studies have looked at the impact of XRT on the stages of TE-I reconstruction. Methods: Patients undergoing TSSM and immediate TE-I reconstruction between 2006 and 2013 were identified from a prospectively maintained database. Rates of TE-I loss and severe infection requiring intravenous antibiotics were compared in patients with prior XRT (85 cases) and PMRT (133 cases). Complications were divided by stage of reconstruction: first stage (TSSM and TE placement) and second stage (TE-I exchange). Results: Mean follow-up time was 2.5 years. Patients with prior XRT had more complications after the first stage of reconstruction than the second (TE-I loss: 15% vs 5%, P = 0.03; infection: 20% vs 8%, P = 0.04). Patients receiving PMRT had low complication rates after the first stage, when they had not yet received radiation (TE-I loss: 2%; infection: 5%). However, complication rates after TE-I exchange (TE-I loss, 18%; infection, 31%) were significantly higher, and nearly 4-fold higher than patients with prior XRT. Conclusions: Patients with prior XRT are at high risk for complications after the first stage of TE-I reconstruction after TSSM; however, the risk of complications at the second stage is comparable to patients without radiation exposure and significantly lower than patients receiving PMRT. Patients receiving radiation therapy should be given appropriate preoperative counseling regarding their risks.